The kinetics of swelling and migration: A case study of plasticized polylactic acid food contact plastics tested with ethanolic food simulants - Viktor Konstantin Dragan; Noémi Petrovics; Csaba Kirchkeszner; Tamás Tábi; Bálint Sámuel Szabó; Zsuzsanna Eke (eXPRESS Polymer Letters, 2024)
The effect of swelling and plasticizer content of a plastic, as well as the ethanol content of the food simulant on the migration kinetics of three stabilizer-type additives from polylactic acid (PLA)-based food contact plastics has been investigated. The results proved that the parameters that affect the diffusion of substances inside the polymer matrix, i.e., swelling, plasticization, and the size of migrants, are the decisive factors in the migration from PLA to ethanolic food simulants. Both swelling and migration were negligible when ethanol 10% (v/v) was used. Contrarily, the specific migration limits of Commission Regulation (European Union, EU) No. 10/2011 were exceeded in ethanol 50% (v/v) for all investigated stabilizers. Migration was promoted by plasticization, but this effect could only be observed when the applied food simulant swelled the plastic (at least 20% (v/v) ethanol content). The dependence of the plasticizer’s migration-enhancing effect on the swelling has not been shown before. When the plasticization caused increased migration, it also led to specific migration limit exceeding within a shorter period of time. It happens even if PLA-based plastics are dedicated to the storage of hydrophilic food, which is the most common application area of these products. These results can support the improvement of both consumer safety and active packaging development.